2016
DOI: 10.1007/s00426-016-0793-y
|View full text |Cite
|
Sign up to set email alerts
|

Familiar units prevail over statistical cues in word segmentation

Abstract: In language acquisition research, the prevailing position is that listeners exploit statistical cues, in particular transitional probabilities between syllables, to discover words of a language. However, other cues are also involved in word discovery. Assessing the weight learners give to these different cues leads to a better understanding of the processes underlying speech segmentation. The present study evaluated whether adult learners preferentially used known units or statistical cues for segmenting conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
2
15
0
1
Order By: Relevance
“…From a theoretical perspective, the effect of prior knowledge is not uniform across all items in the verbal auditory SL task. It could facilitate performance for some items but hinder performance for others, resulting in low internal consistency without necessarily impacting overall success (see also Poulin-Charronnat et al, 2016). Thus, the only difference between the verbal and non-verbal tasks was in the amount of shared variance between items, or, in the extent to which performance in one item predicted performance in other items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a theoretical perspective, the effect of prior knowledge is not uniform across all items in the verbal auditory SL task. It could facilitate performance for some items but hinder performance for others, resulting in low internal consistency without necessarily impacting overall success (see also Poulin-Charronnat et al, 2016). Thus, the only difference between the verbal and non-verbal tasks was in the amount of shared variance between items, or, in the extent to which performance in one item predicted performance in other items.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a relatively large set of studies showing that the expectations that participants bring to SL tasks can be easily manipulated, affecting task performance. For example, pre-exposing participants to isolated words or part-words before the beginning of the familiarization stream has a dramatic effect on SL performance, which can either facilitate (Cunillera, Laine, Camara, & Rodriguez-Fornells, 2010;Lew-Williams, Pelucchi, & Saffran, 2011), or hinder (Perruchet et al, 2014;Poulin-Charronnat, Perruchet, Tillmann, & Peereman, 2016) learning. In the same vein, pre-familiarizing participants with words of different length affects the size of the units they extract from the input (Lew-Williams & Saffran, 2012).…”
Section: The Tabula Rasa Assumptionmentioning
confidence: 99%
“…Learning these particular relations may not change much after the first year of life, when phonetic categories are established and word segmentation is performed (e.g., Kuhl, Williams, Lacerda, Stevens, & Lindblom, 1992;Werker & Tees, 1984). Linguistic auditory tasks are sensitive to prior knowledge in a way that other SL tasks are not (Perruchet, Poulin-Charronnat, Tillmann, & Peereman, 2014;Poulin-Charronnat, Perruchet, Tillmann, & Peereman, 2017;Siegelman, Bogaerts, Elazar, Arciuli, & Frost, 2018), but the effect of that knowledge may not change much after it has been established. Since knowledge about syllable co-occurrences is already present in early childhood (Storkel, 2001), our youngest age group (six-year-olds) may have been too "old" to show age effects.…”
Section: Discussionmentioning
confidence: 99%
“…Familiarization improved subsequent segmentation of the artificial language. Finally, Poulin-Charronnat, Perruchet, Tillmann, and Peereman (2017) found that familiarizing sequences inconsistent with the statistically defined words impaired learning. Thus, short sequences familiarized immediately prior to exposure of an artificial language can constrain segmentation.…”
mentioning
confidence: 98%